Size variations of the calcareous nannofossil taxon Discoaster multiradiatus (Incertae sedis) across the Paleocene–Eocene thermal maximum in ocean drilling program holes 690B and 1209B - F. Tremolada; B. De Bernardi; E. Erba (Marine Micropaleontology, 2008)
Size measurements of the calcareous nannofossil taxon Discoaster multiradiatus were carried out across the Paleocene–Eocene Thermal Maximum (PETM) in Ocean Drilling Program Holes 690B (Maud Rise, Weddell Sea) and 1209B (Shatsky Rise, Pacific Ocean). Morphometric investigations show that D. multiradiatus specimens are generally larger at ODP Site 1209 than at ODP Site 690. A limited increase in size of D. multiradiatus is recorded at ODP Site 1209, whereas significant enlargements characterize ODP Site 690. Preservation is comparable at both sites: nannofossils are moderately preserved with some evidence of etching/overgrowth in the PETM interval. Yet, D. multiradiatus variations do not correlate with preservation state and morphometric data most likely represent primary signals rather than diagenetic artifacts. There is a direct relationship between D. multiradiatus size and paleotemperatures: largest specimens are coeval with global warming associated with the PETM, inferred to result from excess atmospheric CO2 due to (partial) oxidation of massive quantities of methane. Size increases and largest specimens of D. multiradiatus occur at different stratigraphic levels within PETM at ODP Sites 690 and 1209. A marked shift in diameter size was observed at the onset and peak of the Carbon Isotopic Excursion (CIE) at ODP Site 690, but only at the end of CIE and initial recovery interval at ODP Site 1209. This diachroneity is puzzling, but indeed correlates well with reconstructed changes in surface and thermocline water masses temperature and salinity in the PETM interval at low and high latitudes. The presumed high concentrations of carbon dioxide seem to have not influenced the morphometry of D. multiradiatus. The major size increase of D. multiradiatus in the CIE of ODP Site 690 could represent the migration of larger-sized allochtonus specimens that moved from peri-equatorial/subtropical areas to higher latitudes during the warmest interval of the PETM, although no direct evidence of distinct ...